Probability
Full Member
- Joined
- Jan 26, 2012
- Messages
- 432
I have equation (2) of a simultaneous equation;
3a = 2b - 1
I am asked to rearrange it and provide two solutions. OK the second one I got; b = 1/2(3a + 1)
But the first I get; a = 2/3(b - 1)
I can't see a problem with that, yet I am told the answer is; 1/3(b - 1)?
How does dividing both sides by 3 = 1/3 instead of 2/3?
3a = 2b - 1
I am asked to rearrange it and provide two solutions. OK the second one I got; b = 1/2(3a + 1)
But the first I get; a = 2/3(b - 1)
I can't see a problem with that, yet I am told the answer is; 1/3(b - 1)?
How does dividing both sides by 3 = 1/3 instead of 2/3?